ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN SERTA PERANNYA TERHADAP LOYALITAS PELANGGAN PADA CV. REJO MAKMUR - Adhi Wibowo (FEB UNWIKU PURWOKERTO, 2020)
Rejo Makmur is an industrial company that produces rice and also distributing rice for stores in Banyumas. Most customers of CV. Rejo Makmur are retail stores and wholesale rice that are scattered in Banyumas. The purpose of this study was to analyze the factors that affect customer satisfaction and customer loyalty of CV. Rejo Makmur customers in spite of price factors. Factors that analyzed by the researchers is the quality of the product and the assistance provided by the company as information assistance, sales assistance on credit given by the company, and transportation assistance. Primary data obtained from this study using questionnaires. The analysis used for this study were multiple linear regression and simple linear regression. From the analysis it can be concluded that the independent variable is Quality Products, Information Assistance, Credit Sales given by CV. Rejo Makmur, and Transportation Assistance which have positive impact, significant to customer satisfaction and customer satisfaction positive and significant impact on customer loyalty. From the results of multiple linear regression calculations known to the coefficient of determination (R2) of 0.7017 and this shows that the variation of the variable changes of customer satisfaction can be explained by the variable quality of the products, support information, credit sales given by the company, and transportation assistance by 70,17 percent and the remaining 29.83 percent is influenced by other variables not examined. Based on the calculation simple linear regression in mind also the coefficient of determination (R2) of 0.4516 and this means variations in customer loyalty variable change can be explained by the variable customer satisfaction by 45.16 percent and the remaining 54.84 percent is influenced by other variables that are not researched